Semiotics and Graphic Communication: Meaning Matters - Zantides, Evripides (My University, 2025)
Graphic communication is not merely aesthetic; it functions as a system of signs through which meaning is constructed and interpreted. This presentation examines the intersection of semiotics and graphic design, highlighting how colors, shapes, typography, and layout operate as signifiers within cultural and social codes. Drawing on Saussurean and Barthean frameworks, it investigates how meaning is co-constructed between designers and audiences, emphasizing the interplay of intention, interpretation, and context. Case studies of advertising and graphic design applications illustrate how semiotic strategies shape persuasiveness, narrative, and symbolic resonance. In an increasingly image-saturated world, semiotic literacy is essential: it empowers designers to create graphic design that communicates meaningfully, resonate culturally, and influence audiences deliberately.
Keywords: Typography; Semiotics; Graphy Design